A Review on Battery Life and Energy Management in HWSNs using Adaptive Energy Harvesting Techniques - Matthew Iyobhebhe; Abdoulie Momodou S. Tekanyi; K. A. Abubilal; Aliyu D. Usman; H. A. Abdulkareem; Yau Isiaka; E. E. Agbon; Elvis Obi; Chukwudi Ezugwu; Botson Ishaya Chollom; Abubakar Umar; Ajayi Ore-Ofe; Ridwan O. Eleshin; Fatima Ashafa; Paul Thomas Muge (Universitas Negeri Surabaya or The State University of Surabaya, 2025)
This review article scrutinizes the limitations and improvements in battery life and energy management models within HSWNs that employ adaptive energy harvesting techniques. As Wireless Sensor Networks (WSNs) advance into various implementations, including monitoring environmental parameters and smart cities, effective energy management is vital. This review paper examines the responsibility of communication protocols, precisely routing and Medium Access Control (MAC) protocols, in optimizing energy efficiency. We scrutinize existing energy-efficient schemes and their comparative performance, thereby, concentrating on their adaptability to changing energy sources. Examining these protocols, we accentuate the best techniques and potential areas for development. Furthermore, the review highlights the necessity for advanced approaches integrating energy harvesting with resilience communication frameworks to maximize network lifespan. The discoveries are targeted to lead future research and advancement in the field of WSNs, hence, providing more reliable and efficient energy management schemes for WSNs.